ON THE NATURE AND DEVELOPMENT OF SOCIAL PRESENCE IN ONLINE COURSE DISCUSSIONS - Swan, Karen; Shih, Li Fang (Online Learning, 2005)
“Social presence,” the degree to which participants in computer-mediated communication feel affectively connected one to another, has been shown to be an important factor in student satisfaction and success in online courses. This mixed methods study built on previous research to explore in greater depth the nature of social presence and how it develops in online course discussions. The study combined quantitative analyses of survey results from students enrolled in four online graduate courses, and qualitative comparisons of students with the highest and lowest perceptions of social presence. Quantitative results revealed significant correlations between perceived social presence and satisfaction with online discussions, and teased apart the respective influences of the perceived presence of instructors and peers. The findings indicate that the perceived presence of instructors may be a more influential factor in determining student satisfaction than the perceived presence of peers. Correlations with other course and learner characteristics suggest that course design may also significantly affect the development of social presence. Qualitative findings support the quantitative results. In addition, they provide evidence that students perceiving the highest social presence also projected themselves more into online discussions, and reveal meaningful differences in perceptions of the usefulness and purpose of online discussion between students perceiving high and low social presence.